(untitled) (Journal of Management and Social Sciences, 2025)
In today’s competitive business environment, organisations expand globally and face lots of challenges to meet their objectives and choose to be more successful than others. Leaders play significant role in the accomplishment of these goals and boost employees’ performance with attractive and industry-competitive reward system. This paper relies on secondary data for sourcing information and adopts content analysis for analysing its arguments. It also adopts transformational leadership theory. The paper finds that there is a nexus between leadership style and workers’ performance. It also reveals that human resources management strategy has a significant effect on leadership style. It draws a line of correlation between the performance of the JAMB Registrar, Prof. Ishaq Oloyede, and former Chairman of INEC, Prof. Attahiru Jega’s leadership styles, their reward or compensation structure, and the agencies’ service delivery as well. The paper concludes that effective leadership style is one of the sure ways of improving workers’ performance and, as such, should be taken seriously at all levels of management.